EDMODO IMPACTS: MEDIATING DIGITAL CLASS AND ASSESSMENT IN ENGLISH LANGUAGE TEACHING - Aminah, Aminah; Alamanda, Dinda Aprilia; Erfiani, Erfiani; Wati, Wahyuni Kencana; Ihsan, Muhammad Taufik (Jurnal Riset dan Inovasi Pembelajaran, 2021)
This study aims at investigating the impact of the use of Edmodo on the digital class in the English learning assessment. This type of research is the method library research. This study uses journals and articles as reference to collecting data. To answer the literature review, the writer used data that is collected, studied, and treated then combined to get valid and relevant results by using the Internet as a medium to obtain data. In this paper there are three parts used to respond to the literature review: Terminology of Edmodo, Teaching Learning Process and Edmodo, and Edmodo Impact. Research shows that Edmodo's impact on digital classes in the English learning assessments students in the form of learning and made it easier for teachers to convey lessons, content, tasks, and file sharing easy access to all students. And with CBT, it makes it easier for teachers to assess a student's work with computer help. Edmodo became another evaluation so that the results of the examination were objective and accurate. Through Edmodo as a student's performance assessment mode, there is no cheating that students do in studying because students are working independently